2015
DOI: 10.1210/jc.2015-2792
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Transcript Analysis (NETest) in GEP-NETs Treated With Somatostatin Analogs Defines Therapy

Abstract: NETest values (80-100%) were more accurate and occurred at a significantly earlier time point than CgA and predicted SSA treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 39 publications
9
103
0
5
Order By: Relevance
“…Regarding the follow-up phase, recent prospective studies (Cwikla et al 2015, Pavel et al 2017a show that circulating CgA does not represent a valid marker of morphological evolution of disease and has therefore no utility in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the follow-up phase, recent prospective studies (Cwikla et al 2015, Pavel et al 2017a show that circulating CgA does not represent a valid marker of morphological evolution of disease and has therefore no utility in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…More definite evidence about this issue has emerged in the last 2 years, with 2 prospective reports demonstrating the poor capability of CgA changes in reflecting morphological behavior of NENs. In 2015, Cwikla et al (2015) prospectively analyzed a cohort of 28 non-cured gastroenteropancreatic NENs treated with somatostatin analogues (SSA). Considering an at least 25% increase as cut-off, authors found low concordance, namely 64%, between CgA modifications and tumor slope.…”
Section: Assessment Of Morphological Evolution In Patients With Non-cmentioning
confidence: 99%
“…Multianalyte algorithm analysis strategies based upon a 51-gene signature (NETest) have been reported in NETs [24,26,28,29,51,52,53]. This defines the circulating NET ‘fingerprint' [54] and exhibits a higher sensitivity and specificity (98 and 97%, respectively) than secretory markers for identifying neoplasia [25,51].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the PCR methodology, mathematical analysis and validation have been published in detail [24,26,28,29]. The procedure utilizes a 2-step protocol (RNA isolation, cDNA production and PCR) [24,28] from EDTA-collected whole blood [24,28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation